2001
DOI: 10.1016/s0008-6363(00)00256-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in density of transverse tubules and L-type Ca2+ channels in canine tachycardia-induced heart failure

Abstract: Cellular remodeling in heart failure results in decreased density of T-tubules and L-type Ca(2+) channels, which contribute to abnormal EC coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
219
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(246 citation statements)
references
References 41 publications
24
219
2
1
Order By: Relevance
“…Schroder et al (39) found that single Ca 2ϩ channels exhibited increased availability and opening probability in cells isolated from failing human hearts, but whole cell I Ca,L did not show significant differences, when compared with nonfailing cells, in agreement with a previous report in humans (27). Recently, it has been found that the L-type Ca 2ϩ channel number is reduced and channel open times are increased in ventricular cells from pacing-induced canine failing hearts, so that overall I Ca,L density is unchanged (10). The results of the present study showed no significant change in I Ca,L density and kinetics in cells from the endocardium, midmyocardial layer, and epicardium, consistent with other reports in the same model and species (13).…”
Section: Discussionsupporting
confidence: 91%
“…Schroder et al (39) found that single Ca 2ϩ channels exhibited increased availability and opening probability in cells isolated from failing human hearts, but whole cell I Ca,L did not show significant differences, when compared with nonfailing cells, in agreement with a previous report in humans (27). Recently, it has been found that the L-type Ca 2ϩ channel number is reduced and channel open times are increased in ventricular cells from pacing-induced canine failing hearts, so that overall I Ca,L density is unchanged (10). The results of the present study showed no significant change in I Ca,L density and kinetics in cells from the endocardium, midmyocardial layer, and epicardium, consistent with other reports in the same model and species (13).…”
Section: Discussionsupporting
confidence: 91%
“…Such knowledge is in great need for effective development of new diagnostic, prognostic, and therapeutic tools for HF, an endstage cardiac disease with poor clinical prognosis. The pathophysiologic hallmark of HF is a weakened cardiac calcium transient (Gómez et al, 1997;Litwin et al, 2000;Gómez et al, 2001), which can be attributed to t-tubule remodeling (Lyon et al, 2009;Louch et al, 2010;Wei et al, 2010) and dyad uncoupling (Gómez et al, 1997;Gómez et al, 2001;He et al, 2001;Louch et al, 2006;Bito et al, 2008;Louch et al, 2010). T-tubule remodeling marks the transition from hypertrophy to failure (Wei et al, 2010), contributing to the progression of HF (see reviews in (Brette and Orchard, 2003;Brette and Orchard, 2007;Louch et al, 2010;Ferrantini et al, 2013;Guo et al, 2013;Ibrahim and Terracciano, 2013)).…”
Section: Bin1 In Heart Failure Progressionmentioning
confidence: 99%
“…Although the canine tachycardia HF model has been used to characterize pathophysiological changes in HF and to explore the roles of individual genes/ proteins in pathogenesis of HF [9][10][11][12][13][14], genome-wide expression analyses to identify pathways/ networks that underlie the molecular genesis of the HF phenotype in this model have not been performed.…”
Section: Introductionmentioning
confidence: 99%